Santri Merawat Tradisi Lokal (Studi atas Kompolan Tera’ Bulan di Kecamatan Gapura) - Bambang Ilyasin (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
This research departs from the statement that santri are considered to have a role in maintaining and preserving local traditions, armed with the knowledge and experience gained at the pesantren. This can be seen in the Kompolan Tera' Bulan in Gapura Sumenep District. This study aims to describe the efforts and activities carried out by santri in maintaining local traditions in Kompolan Tera' Bulan. The questions to answer include: How do santri take care of local traditions? What is the role of santri in taking care of traditions in Kompolan Tera' Bulan? and what are the impacts of taking care of traditions in Kompolan Tera' Bulan? The data in this paper were obtained through observation, interviews, and documentation to active members of Kompolan Tera' Bulan, which were then classified, reduced, and analysed in depth. In the end, it was found that santri have various ways to maintain local traditions in Kompolan Tera' Bulan, such as socialising local traditions, encouraging the implementation of local traditions, providing examples in maintaining local traditions, creating local culture as an identity, caring for the environment, direct practice of parts of the tradition consistently, and instilling faith in the community. In Kompolan Tera' Bulan activities, santri have three roles in maintaining local traditions, that is acting as leaders, as mobilisers in the community, and as motivators or encouragers. In addition, there are at least five real impacts of maintaining local traditions in Kompolan Tera' Bulan, that are: strengthening friendship, encouraging the implementation of routine community gatherings, raising public awareness of the importance of models such as Kompolan Tera' Bulan, preserving local traditions, becoming a forum for forging various knowledge, especially regarding cultural locality.